2016
DOI: 10.1002/2016ja023122
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric storm effects and equatorial plasma irregularities during the 17–18 March 2015 event

Abstract: The intense magnetic storm on 17–18 March 2015 caused large disturbances of the ionosphere. Based on the plasma density (Ni) observations performed by the Swarm fleet of satellites, the Gravity Recovery and Climate Experiment mission, and the Communications/Navigation Outage Forecasting System satellite, we characterize the storm‐related perturbations at low latitudes. All these satellites sampled the ionosphere in morning and evening time sectors where large modifications occurred. Modifications of plasma den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
3
34
0
Order By: Relevance
“…In the previous studies concerning EPBs in the recovery phase, the enhancement of the S4 index was observed during postmidnight period in the African and South American region in the 2015 St. Patrick's Day storm Carter et al 2016. In association with an intense storm, the density variations in the early morning were observed by the C/NOFS satellite (Zhou et al 2016). Comparing these previous studies, EPBs #13 and #14 were observed before midnight, which is the typical time zone for an EPB occurrence.…”
Section: Discussionmentioning
confidence: 85%
“…In the previous studies concerning EPBs in the recovery phase, the enhancement of the S4 index was observed during postmidnight period in the African and South American region in the 2015 St. Patrick's Day storm Carter et al 2016. In association with an intense storm, the density variations in the early morning were observed by the C/NOFS satellite (Zhou et al 2016). Comparing these previous studies, EPBs #13 and #14 were observed before midnight, which is the typical time zone for an EPB occurrence.…”
Section: Discussionmentioning
confidence: 85%
“…This Special Section achieved new insights into the storm time behavior of PPEF and disturbance dynamo electric field (DDEF) effects. Various observational studies deal with dynamical ionospheric changes at different geospace regimes, from subauroral to middle and low latitudes [ Hairston et al ., ; Huang et al ., ; Kalita et al , ; Kuai et al ., ; Zhou et al ., ; Zhang et al , ; etc]. Hairston et al [] provided a comprehensive view of the DMSP and C/NOFS measurements of the global evolution of plasma drifts (electric fields) during the March 2015 storm.…”
Section: Main Results: Geospace Responses To the St Patrick's Day Stmentioning
confidence: 99%
“…The St. Patrick's Day storm was so far the largest storm occurring during the solar cycle 24 (minimum SYM-H value reached À234 nT). The ionospheric responses as well as the plasma irregularities and related scintillation at low latitudes have been discussed by previous studies (e.g., Astafyeva et al, 2015;Carter et al, 2016;Zhou et al, 2016). Focusing at high latitudes, Liu et al (2016) has compared the development of SED and TOI between measurements of global TEC map and model predictions.…”
Section: Overview Of the 2015 St Patrick's Day Stormmentioning
confidence: 97%